The study of functional and metabolic continuum by metabolism parameters in blood plasma of healthy people as compared with patients with type 2 diabetes and hypertension against the background of type 2 diabetes - Gozhenko, A. I.; Hryshko, Yu. M.; Gorbach, T. V. (Journal of Education, Health and Sport, 2019)
It is known that existing systems of regulation of energy homeostasis provide adequate needs of the body, depending on both the receipt and use of energy. Moreover, the organization of energy supply has its own characteristics in insulin-dependent and insulin-independent tissues. The main thing in the organization of energy supply is the achievement of the principle of compliance with the functional needs of the body, that is, the maintenance of the functional and metabolic continuum (FMC) We studied the metabolic parameters of FMC in healthy people and patients with type 2 DM and patients with hypertension against the background of type 2 DM according to the study of some indicators of blood plasma. The identified features, in our opinion, are one of the first manifestations of FMC disorder due to insulin resistance With the advent of insulin deficiency, there are increasing disturbances of energy metabolism, which are mainly caused by endothelial dysfunction and neuro-hormonal regulatory shifts of a stressful nature. The consequences or manifestations of these processes can probably be found in all environments of the body: blood, saliva, condensed air, that is, they have a systemic character.